2017
DOI: 10.1186/s12991-017-0161-3
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-1: a possible marker for emotional and cognitive disturbances, and treatment effectiveness in major depressive disorder

Abstract: Depression and cognitive dysfunction share a common neuropathological platform. Abnormal neural plasticity in the frontolimbic circuits has been linked to changes in the expression of neurotrophic factors, including IGF-1. These changes may result in clinical abnormalities observed over the course of major depressive disorder (MDD), including cognitive dysfunction. The present review aimed to summarize evidence regarding abnormalities of peripheral IGF-1 in MDD patients and assess a marker and predictive role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 58 publications
(123 reference statements)
5
29
1
Order By: Relevance
“…In human acromegaly patients, recent studies have reported cognition deficits, decreased short-term and long-term memory, anxiety and impaired decision making, and decreased activities in pre-frontal and mid-temporal cortices in brain (274,275,276,277). Interestingly, recent reports and multiple meta-analyses directly implicate a higher than normal serum IGF-1 as a disease trait marker in major depressive disorder (MDD) and bipolar disorder (BD) further stimulating the pleiotropy of GH action in cognitive development and maintenance (278,279,280,281).…”
Section: Cognitive Studies In Humans With Ghr Deficiencymentioning
confidence: 99%
“…In human acromegaly patients, recent studies have reported cognition deficits, decreased short-term and long-term memory, anxiety and impaired decision making, and decreased activities in pre-frontal and mid-temporal cortices in brain (274,275,276,277). Interestingly, recent reports and multiple meta-analyses directly implicate a higher than normal serum IGF-1 as a disease trait marker in major depressive disorder (MDD) and bipolar disorder (BD) further stimulating the pleiotropy of GH action in cognitive development and maintenance (278,279,280,281).…”
Section: Cognitive Studies In Humans With Ghr Deficiencymentioning
confidence: 99%
“…It is involved in cell growth, differentiation, and maturation (through DNA synthesis and mitosis stimulation), in metabolic (i.e., glucose uptake and protein production) [13] and neuroplastic processes (synapses formation, neurotransmitters releasing, and exciting of neurons) [12]. Due to IGF-1 pleiotropic functions, it has been assumed that impairments in the IGF-1 system might be responsible for some aspects of MDD pathogenesis [13], as well as peripheral IGF-1 levels could have the marker value [14]. According to our recent review [14], the majority of studies demonstrate higher concentrations of peripheral IGF-1 in MDD patients compared to healthy controls (HC).…”
Section: Introductionmentioning
confidence: 99%
“…A growing amount of evidence indicates the pathogenic influence of insulin-like growth factor 1 (IGF-1) on a major depressive disorder (MDD) ( 95 ). Most of the studies showed that increased peripheral IGF-1 levels might predict the occurrence of MDD, whereas decreased IGF-1 levels might reflect the treatment effectiveness ( 96 ). Nevertheless, Yue et al found no differences in serum IGF-1 concentrations in PSD patients as opposed to non-depressed poststroke patients and persons with MDD ( 97 ).…”
Section: Molecular Biomarkers Of Psdmentioning
confidence: 99%